1990
DOI: 10.1080/01411599008207946
|View full text |Cite
|
Sign up to set email alerts
|

Structural phase transition induced by elastic fields of impurities

Abstract: Results of a theoretical and experimental study of cooperative behaviour in soft lattices with off-center ions characterized by elastic dipole moments are presented. The influence of random elastic fields on the impurity-induced ferroelectric phase transition is investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Indeed, the coupling between a quadrupole at a K site and an ordered array of quadrupoles is allowed by symmetry, in contrast with the dipole analogue. As in the latticedynamical model, only detailed knowledge of the interaction forces allows one to judge whether this approach predicts condensation into an ordered or disordered state (see also Glinchuk and Smolyaninov (1990)).…”
Section: Microscopic Origin O F Polar Configuration In Ktao3 : LImentioning
confidence: 99%
“…Indeed, the coupling between a quadrupole at a K site and an ordered array of quadrupoles is allowed by symmetry, in contrast with the dipole analogue. As in the latticedynamical model, only detailed knowledge of the interaction forces allows one to judge whether this approach predicts condensation into an ordered or disordered state (see also Glinchuk and Smolyaninov (1990)).…”
Section: Microscopic Origin O F Polar Configuration In Ktao3 : LImentioning
confidence: 99%
“…As a result, the QPE do not undergo a phase transition, and the paraelectric state persists down to the lowest temperatures, T → 0 [1]. Nevertheless, the ferroelectric phase transition can be induced by the introduction of even small concentrations of impurities (of dipole [2,3] or quadrupole [4] type) or application of uniaxial stress [5]. Usually, it is suggested that the ferroelectric phase transition in the QPE can be induced by local symmetry-breaking (SB) defects [2,3], or the soft non-symmetry-breaking (NSB) defects that lead to an increase of the local ferroelectric transition temperature [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, the studies of the three-dimensional lattice ϕ 4 -model with NSB defects [9][10][11] have shown that NSB defects (and hard NSB defects also) and/or anharmonicity of the pure lattice can give rise to a dynamic transition from an ergodic to a non-ergodic state. The non-ergodic state is characterized by the formation of a long-time correlation (LTC) of the fluctuations of the lattice distortions for T d > T c , which correspond to the appearance of quasi-static displacements (precursor order clusters).…”
Section: Introductionmentioning
confidence: 99%